Factors Promoting Speech: Analysis of Output During Discussion Activities - Shinozaki, Fumiya; Yokoyama, Satoshi (LPPM Universitas Advent Indonesia, 2023)
Sixty-one junior high school students in Japan participated twice in an online English group conversation lesson. At the first half of a session, each student gave an individual presentation to a Filipino instructor and the other group members. At the second half of the session, they conducted discussions, where the instructor, as the facilitator, asked each student relevant questions. The present study first determined if there would be a change in the maximum number of words spoken in discussions between the first and second online English conversation lessons. As the result of a statistical analysis for the discussions, there was a significant difference between the maximum number of words spoken during the two discussions. Since a significant change was admitted, a further discussion was conducted to clarify the reasons for the change. The factors of the increase in words spoken were discussed in terms of willingness to communicate, having things to communicate, anxiety, confidence, and instructors’ intervention. All of them were thought to affect the increase. The findings suggest that (1) it is important to set some activities for students to strengthen their own opinions about topics in advance and (2) it is effective not to end with a single practice but to provide at least two opportunities for the output and interaction with others.